Profile of Creative Thinking of Students with Mathematical Logical Intelligence in Solving Function Composition - Rita Lefrida; Musdalifa; Sukayasa (Universitas Teknokrat Indonesia, 2025)
Creative thinking in students is essential in the learning process. It can help students discover new ways to understand and solve problems. Through creative thinking, students do not merely focus on finding the correct answer but also learn to explore various possibilities and ideas. This study aims to obtain a description of students’ creative thinking profiles with logical-mathematical intelligence in solving mathematical problems, viewed from their learning styles. The focus is on how students with logical-mathematical intelligence utilize creative thinking in accordance with their individual learning styles. This research employs a qualitative approach. The research subjects are three 10th-grade high school students, each representing a combination of logical-mathematical intelligence with a different learning style: visual, auditory, and kinesthetic. Data were collected through students’ written responses and interviews. The results of the study show that at the stage of understanding the problem, subjects with logical-mathematical intelligence across all three learning styles demonstrated aspects of fluency and flexibility. At the planning stage, the visual and kinesthetic learners met all aspects of creative thinking, including fluency, flexibility, and novelty. In contrast, the auditory learner demonstrated only fluency and flexibility. At the stage of carrying out the plan, visual and kinesthetic learners again showed all aspects of creative thinking more completely than the auditory learner, who only demonstrated fluency and flexibility. However, in the reviewing stage, all subjects showed only fluency and flexibility, without the presence of novelty. These findings highlight the importance of considering students’ learning styles in developing creative thinking skills, particularly for those with logical-mathematical intelligence. An effective learning process must be designed with differentiation, taking into account students’ learning styles. With appropriate strategies, students can not only understand the material well but also fully develop their creative thinking potential at each stage of problem-solving.